Van der Waals gas as working substance in a Curzon and Ahlborn-Novikov engine - Delfino Ladino-Luna (Entropy, 2005)
Abstract: Using a van der Waals gas as the working substance the so called Curzon and Ahlborn-Novikov engine is studied. It is shown that some previous results found in the literature of finite time thermodynamics can be written in a more general form, means of this gas and by taking a non linear heat transfer law.